Gender differentials in maths test scores in MENA countries - Menshawy Badr; Oliver Morrissey; Simon Appleton (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2012)
This paper investigates gender inequality of academic achievement using mean and quantile decomposition analysis in eight selected MENA countries. We use data from TIMSS 2007 to decompose the test scores gap between boys and girls at the eighth grade. There is a mixed picture of gender inequality across the eight countries; the gap favours boys in three, favours girls in three and there is no average difference in two countries. No particular factors consistently explain gender inequality in test scores across MENA. In general, although family characteristics tend to favour girls (in most countries their characteristics suggest they should perform better than boys) the returns to education tend to favour boys (they get a higher test score for given characteristics); the educational system appears to favour boys.
Keywords: I21; O15; O53; 330; Educational Attainment; Maths Test Scores; Gender Differentials; MENA